(2x+y)dx+(x+y+1)dy=0

Simple and best practice solution for (2x+y)dx+(x+y+1)dy=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2x+y)dx+(x+y+1)dy=0 equation:


Simplifying
(2x + y) * dx + (x + y + 1) * dy = 0

Reorder the terms for easier multiplication:
dx(2x + y) + (x + y + 1) * dy = 0
(2x * dx + y * dx) + (x + y + 1) * dy = 0

Reorder the terms:
(dxy + 2dx2) + (x + y + 1) * dy = 0
(dxy + 2dx2) + (x + y + 1) * dy = 0

Reorder the terms:
dxy + 2dx2 + (1 + x + y) * dy = 0

Reorder the terms for easier multiplication:
dxy + 2dx2 + dy(1 + x + y) = 0
dxy + 2dx2 + (1 * dy + x * dy + y * dy) = 0

Reorder the terms:
dxy + 2dx2 + (dxy + 1dy + dy2) = 0
dxy + 2dx2 + (dxy + 1dy + dy2) = 0

Reorder the terms:
dxy + dxy + 2dx2 + 1dy + dy2 = 0

Combine like terms: dxy + dxy = 2dxy
2dxy + 2dx2 + 1dy + dy2 = 0

Solving
2dxy + 2dx2 + 1dy + dy2 = 0

Solving for variable 'd'.

Move all terms containing d to the left, all other terms to the right.

Factor out the Greatest Common Factor (GCF), 'd'.
d(2xy + 2x2 + y + y2) = 0

Subproblem 1

Set the factor 'd' equal to zero and attempt to solve: Simplifying d = 0 Solving d = 0 Move all terms containing d to the left, all other terms to the right. Simplifying d = 0

Subproblem 2

Set the factor '(2xy + 2x2 + y + y2)' equal to zero and attempt to solve: Simplifying 2xy + 2x2 + y + y2 = 0 Solving 2xy + 2x2 + y + y2 = 0 Move all terms containing d to the left, all other terms to the right. Add '-2xy' to each side of the equation. 2xy + 2x2 + y + -2xy + y2 = 0 + -2xy Reorder the terms: 2xy + -2xy + 2x2 + y + y2 = 0 + -2xy Combine like terms: 2xy + -2xy = 0 0 + 2x2 + y + y2 = 0 + -2xy 2x2 + y + y2 = 0 + -2xy Remove the zero: 2x2 + y + y2 = -2xy Add '-2x2' to each side of the equation. 2x2 + y + -2x2 + y2 = -2xy + -2x2 Reorder the terms: 2x2 + -2x2 + y + y2 = -2xy + -2x2 Combine like terms: 2x2 + -2x2 = 0 0 + y + y2 = -2xy + -2x2 y + y2 = -2xy + -2x2 Add '-1y' to each side of the equation. y + -1y + y2 = -2xy + -2x2 + -1y Combine like terms: y + -1y = 0 0 + y2 = -2xy + -2x2 + -1y y2 = -2xy + -2x2 + -1y Add '-1y2' to each side of the equation. y2 + -1y2 = -2xy + -2x2 + -1y + -1y2 Combine like terms: y2 + -1y2 = 0 0 = -2xy + -2x2 + -1y + -1y2 Simplifying 0 = -2xy + -2x2 + -1y + -1y2 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

Solution

d = {0}

See similar equations:

| 17-3z=z-1 | | 5p=5p-15 | | 980n=361 | | 308-11x=8x | | 575980x=130361 | | 575980x=361 | | 8/3x=-16/3 | | =361 | | 980=361 | | a=18+7a | | 5z-3(z-7)=2+3z | | 100=5/8X | | 32-4x=20 | | 12n-8-2n+10-3= | | 8d+2e+5e= | | (sin((17x))^1/2 | | 2r-5=n(n-4) | | 7s+43=141 | | 2/3x2/3x23 | | 4x-10=11-3x | | (2b+4)=10(3b-20) | | cosx=0.42 | | -(3a+5a^2)+5a=0 | | 12(3x-5)=94 | | 1/8(x-1)3-8=0 | | -(-5xy^2)*3x^3y^4=0 | | X=-6a+2b | | =b^2+13b+30 | | -a^3+3a^7=0 | | 5x^2+3y^2+3(x^2-y^2)=0 | | n-3=43 | | 3-x=7+3x |

Equations solver categories